SMEs' tax compliance costs and IT adoption: the case of a value-added tax - Che Azmi, A.A.; Sapiei, N.S.; Mustapha, M.Z.; Abdullah, M. (Elsevier, 2016)
The objective of this study is to examine the factors behind the adoption of a tax-compliant accounting system among small and medium-sized enterprises (SMEs) using the technological–organizational–environmental (TOE) framework, particularly the role of tax compliance costs in fostering the adoption of this system. This study makes a novel contribution by attempting to link the influence of tax compliance costs to the information technology (IT) adoption literature. Questionnaires were distributed to 401 SMEs, and data were analyzed using partial least squares. The results suggest that the TOE framework is useful for examining factors that affect SMEs' IT adoption decisions; the influence of perceived compatibility, complexity, relative advantage, and mimetic and regulatory pressure is important for the adoption of a value-added tax (VAT)-compliant accounting system. Moreover, the impact of compatibility, learning from external sources, and perceived coercive pressure on the adoption of a VAT-compliant accounting system is moderated by tax compliance cost.